TATHWIR MANHAJ TA'LIIM AL LUGAH AL 'ARABIYYAH AL ITTISOLIYYAT BI DAAR MUHIBBI AL 'ARABIYYAH AL JAAMI'AH AL ISLAMIYYAH AL HUKUUMIYYAH PEKALONGAN - M. Fairuz Rosyid; Nur Syahid (Universitas Islam Negeri Mataram, 2020)
The purpose of this research to examine the development ofcommunicative curriculum conducted by arabic institutions Dar MuhibAl-‘Arobiyah. The data were collected through correspondence anddocumentation. The method of this research is qualitative, the data analysisuses data triangulation, that is: data reduction, data presentation, andconclusion. The primary data sources in this study were teachers, students,and curriculum documents. The result of this research can be concluded thatthe development of communicative arabic language Dar Muhibbi al ’Arabiyyahstated not effective. It cause the methods, media, and evaluations used thatare used not relevant to the communicative objectives that have been decided.The Methods, media, and evaluations are more directed to memorizing manyvocabulary thah the practice of using sentences in dialogue. Suggestions: 1)The communicative learning focused on the process of producing senteceswith multiplying conversations; 2)The asatidz/teachers to apply the processof developing curriculum by existing frameworks example, Hilda Tabamodel.